ЛОКАЛЬНІ АВТОНОМНІ ДЖЕРЕЛА ЕНЕРГОПОСТАЧАННЯ ДЛЯ УМОВ НАДЗВИЧАЙНИХ СИТУАЦІЙ - Чорний, О.П.; Зачепа, Ю.В.; Мазуренко, Л.І.; Буряковський, С.Г.; Ченчевой, В.В.; Зачепа, Н.В. (Інститут електродинаміки НАН України, Київ, 2020)
Dynamic modes of operation of a local autonomous energy source with the connection of the main typical consumers of electricity are investigated. The overload capacity of a local autonomous power source, formed from electrical equipment of other functional purpose on the basis of an asynchronous machine with capacitive self-excitation, is determined. The conditions for the implementation of "favorable" switching during startup of motors of comparable power have been established and the expediency of using start-up systems and systems of pre-start boosting excitation of the electric generator in the autonomous power supply source has been substantiated. References. 6, figures 3, table 2.